Associations Between Extreme Temperatures and Cardiovascular Cause-Specific Mortality: Results From 27 Countries - Alahmad, Barrak; Khraishah, Haitham; Royé, Dominic; Vicedo-Cabrera, Ana Maria; Guo, Yuming; Papatheodorou, Stefania; Achilleos, Souzana; Acquaotta, Fiorella; Armstrong, Ben; Bell, Michelle L; Pan, Shih-Chun; de Sousa Zanotti Stagliorio Coelho, Micheline; et al. (My University, 2023)
Cardiovascular disease is the leading cause of death worldwide. Existing studies on the association between temperatures and cardiovascular deaths have been limited in geographic zones and have generally considered associations with total cardiovascular deaths rather than cause-specific cardiovascular deaths.
Keywords: climate change; cold temperature; heart failure; heat; hot temperature; myocardial ischemia; stroke